Coordination chemistry of Cu(II), Co(II), Zn(II) and Ag(I) complexes of isomeric pyridine 2- and 4-carboxamides and their biological activity evaluation. (8th May 2017) - Lumb, Isha; Sran, Balkaran Singh; Sood, Henna; Arora, Daljit Singh; Hundal, Geeta
Graphical abstract: Eight complexes of Cu(II), Co(II), Zn(II) and Ag(I) ions with the rarely studied ligands, N, N-diisopropyl/butylpicolinamide (L1 /L2 ) and N, N-diisopropyl/butylisonicotinamide (L3 /L4 ), have been synthesized and characterized spectroscopically, and their molecular and crystal structures have been reported. Diverse coordination modes of these positional isomers have been discovered, discussed and compared with the limited available literature in the light of their respective convergent and divergent nature. Abstract: Eight complexes of Cu(II), Co(II), Zn(II) and Ag(I) with rarely studied ligands, N, N-diisopropyl/butylpicolinamide (L1 /L2 ), and N, N-diisopropyl/butylisonicotinamide (L3 /L4 ), have been synthesized and characterized spectroscopically, and their molecular and crystal structures have been reported. Diverse coordination modes of these positional isomers have been discovered, discussed and compared with the limited available literature in light of their respective convergent and divergent nature. All the complexes show stable and extended 1D, 2D or 3D coordination/H-bonded networks owing to a large number of weak C–H⋯O/X and other intermolecular interactions. Further, the ligands as well as the metal complexes have been evaluated for their antimicrobial activity and have turned out to be potent antimicrobial agents.